2021
DOI: 10.1097/ccm.0000000000004943
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Authority During Tele-ICU Care Reduces Mortality and Length of Stay—A Systematic Review and Meta-Analysis*

Abstract: OBJECTIVES: Although the current coronavirus disease 2019 pandemic demonstrates the urgent need for the integration of tele-ICUs, there is still a lack of uniform regulations regarding the level of authority. We conducted a systematic review and meta-analysis to evaluate the impact of the level of authority in tele-ICU care on patient outcomes. DATA SOURCES: We searched MEDLINE, EMBASE, CENTRAL, and Web of Science from inception until August 30, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…The characteristics of ICU telemedicine programs to improve efficiency as measured by ICU length of stay is becoming clearer. Telemedicine programs that provide expert mentoring and direct management services are more effective (70, 71) than programs that provide consultative advice alone (72, 73). The interventional approach has enabled earlier recognition and provided management support for patients with time-sensitive high-risk conditions including stroke (74) and sepsis (75).…”
Section: The Healthcare Landscapementioning
confidence: 99%
“…The characteristics of ICU telemedicine programs to improve efficiency as measured by ICU length of stay is becoming clearer. Telemedicine programs that provide expert mentoring and direct management services are more effective (70, 71) than programs that provide consultative advice alone (72, 73). The interventional approach has enabled earlier recognition and provided management support for patients with time-sensitive high-risk conditions including stroke (74) and sepsis (75).…”
Section: The Healthcare Landscapementioning
confidence: 99%
“…Though several studies from the United States (US) have shown that telemedical treatment support might reduce ICU and hospital mortality and length of stay (LOS) [ 5 7 ], two studies (one single-centre and one multicentre trial) revealed that telemedicine improved adherence to best-practice measures like deep vein thrombosis prevention and infectious disease management [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remote monitoring and care have allowed for increased vigilance for patient deterioration while expanding the capacity of smaller units and decreasing staff burnout [ 5 ]. When decision-making resides with remote critical care specialists, mortality and length of stay are reduced [ 6 ].…”
Section: Introductionmentioning
confidence: 99%